1972
DOI: 10.1139/m72-306
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymic in vitro formation of nitrosamines by bacteria isolated from meat products

Abstract: The formation in culture of dimethyl- and diethyl-nitrosamine from sodium nitrite and secondary amines was brought about by Streptococcus species, but not by members of several other genera tested. This formation appears to be non-enzymic, pH dependent, and may be catalyzed by one or more bacterial metabolic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Nitrosation of dimethylamine by rat intestinal flora (14,15) and of dimethylamine and piperidine by Escherichia coli (16) was also found to be partially heat-labile. In some other microbial nitrosation systems, however, boiled cells were as effective as live ones (6,17,18).…”
Section: Experiments 4) No Difference Was Observedmentioning
confidence: 99%
“…Nitrosation of dimethylamine by rat intestinal flora (14,15) and of dimethylamine and piperidine by Escherichia coli (16) was also found to be partially heat-labile. In some other microbial nitrosation systems, however, boiled cells were as effective as live ones (6,17,18).…”
Section: Experiments 4) No Difference Was Observedmentioning
confidence: 99%
“…Il fatto che la nitrosazione si verifichi a pH prossimi alla neutralità indicherebbe che il processo è di tipo enzimatico, sebbene non siano stati recuperati enzimi liberi (esoenzimi) 80 . 36 , ma non sono state trovato prove che supportassero la natura enzimatica della reazione. 36 , ma non sono state trovato prove che supportassero la natura enzimatica della reazione.…”
Section: Nitrosammineunclassified
“…The fact that nitrosation occurred at near-neutral pH values was taken to indicate that the process was enzymatic, although no cell-free enzyme was obtained (41). Several species of catalasenegative cocci, including E. faecalis, E. faecium, and L. lactis, have been shown to be capable of forming nitrosamines, but the other lactic acid bacteria and pseudomonads tested did not (15). These investigators found no evidence for an enzymatic reaction.…”
Section: Nitrosaminesmentioning
confidence: 99%